The use of radiography for diagnosis of apical infection of equine cheek teeth. (23rd June 2015) - Isgren, C. M.; Townsend, N. B.
Summary: Despite recent developments in advanced imaging, radiography remains the most commonly employed imaging modality for investigating apical infection of cheek teeth in horses. Radiographic technique, knowledge of the normal anatomy and horse compliance are paramount for acquiring good quality dental radiographs. Interpretation of subtle pathology can be difficult for even the most experienced radiologist; however, in more chronic cases, identification of dental abnormalities is easier.